Konsep Motivasi Personalia Dalam Manajemen Pendidikan Islam - Samsirin Samsirin (At-Ta'dib, 2016)
The existence of a motivation is very important for an organizationto maximize the effectiveness and productivity levels. Therefore, many ofthe figures that explain the concept of motivation, including McClelland,Tery, Abraham Sperling and Robert A Baron. In an effort to improve theefficiency and effectiveness of institutions, personnel productivity get themost attention from several parties. Personnel could process the brainactively and be agile, have advanced desire, high curiosity, energetic,systematic analysis, open to receive opinions, high initiative, and the broadmind focused. Motivation is a condition that drives self-directed of personnelto achieve the objectives of the institution. it is a main state in a person thatencourage, activate and move the behavior on goal. Therefore Motivationhas a very close relationship with intention. Intention in Islam has twofunctions, authorize the acts of worship. And differ a worship activitiesand which doesn’t. This Papers discuss the concepts of personnal motivationand associat it with the Islamic Education, this paper concluded thatpersonal motivation is the process of influencing and encouraging a personto complete the desired goals and to create the passion of one’s work to getthem to cooperate. and in Islamic education, personal motivation in doingof duty is an act of worship.